Upregulation of S100P, receptor for advanced glycation end products and ezrin in malignant melanoma. Issue 12 (4th December 2013) - Zhu, Li; Ito, Takamichi; Nakahara, Takeshi; Nagae, Konosuke; Fuyuno, Yoko; Nakao, Masayoshi; Akahoshi, Maki; Nakagawa, Rieko; Tu, Yating; Uchi, Hiroshi; Furue, Masutaka
Abstract S100P is a member of the S100 family. Increased levels of S100P have been documented in various malignancies. Binding of extracellular S100P to receptor for advanced glycation end products (RAGE) or coupling of intracellular S100P with a cytoskeletal protein, ezrin, play a crucial role in tumor growth, invasion and metastasis. However, little is known about the expression of S100P, RAGE and ezrin in malignant melanoma. We immunostained these three molecules in 20 primary and 20 metastatic melanomas. Samples of 20 benign nevus pigmentosus and 10 of normal skin were tested as controls. The expression levels (percentage of positively stained cells) of S100P, RAGE and ezrin were significantly higher in melanomas than in nevus pigmentosus. Moreover, slightly but significantly higher expression levels were observed in metastatic than in primary melanomas. Significant positive correlations were evident between the expression levels of S100P and RAGE, S100P and ezrin, and RAGE and ezrin, respectively. In conclusion, the coordinate upregulation of S100P, RAGE and ezrin may possibly facilitate malignant transformation of melanoma.